Financial Record Keeping Practices on Growth of Small and Medium Enterprises. A Case Study of Kisaasi Market, Kampala Gayaza Road - Ines Simon Peter (Uganda Christian University, 2026)
This study investigated the effect of financial record-keeping practices on the growth of SMEs in Kisaasi Market. Specifically, it assessed the influence of daily sales records, profit and loss records, and expense records on SME growth indicators such as sales increase, profit improvement, business expansion, employment growth, asset accumulation, customer base expansion, and perceived benefits from record-keeping. The research adopted a descriptive cross-sectional design with a quantitative approach. The target population comprised 80 registered SMEs in Kisaasi Market. Using Yamane’s formula, a sample of 56 respondents was selected through purposive and simple random sampling. Correlation analysis showed significant positive relationships between all three record-keeping practices and SME growth (r = 0.58 for daily sales, r = 0.64 for profit/loss, r = 0.55 for expenses; all p < 0.01). Multiple regression results indicated that the three practices jointly explained 48.2% of the variance in SME growth (R2 = 0.482, p = 0.000). Profit and loss records exerted the strongest influence (β = 0.38, p = 0.001), followed by daily sales records (β = 0.29, p = 0.010) and expense records (β = 0.22, p = 0.046). The study concludes that financial record-keeping practices significantly and positively influence SME growth in Kisaasi Market, with profit and loss records playing the most critical role. However, persistent gaps in formal profit tracking and expense discipline limit faster expansion and employment creation. Recommendations include: (1) SME owners adopting simple monthly profit summaries and separating personal/business funds; (2) market associations organising short practical training sessions; (3) government providing free basic record-keeping tools and simplified tax education; and (4) financial institutions accepting simple records for small loans. These targeted interventions could strengthen financial discipline and accelerate SME growth in similar informal urban markets.
Undergraduate